Strategi Pemasaran untuk Meningkatkan Penghasilan UMKM di Sua Snack Tembung - Miftahul Jannah Hasibuan; Nursantri Yanti; Waizul Qarni (Universitas 17 Agustus 1945 Semarang, 2023)
This research aims to find out how marketing strategies can increase MSME income at SUA Snack Tembung. And what are the opportunities and obstacles for marketing strategies to increase MSME income at SUA Snack Tembung. This type of research is qualitative research. In this research the author takes a descriptive approach or strategy, namely describing or depicting an object, as well as a phenomenon in a social setting and expressed in the form of writing and sentences or it can also be interpreted as telling the situation of the research according to the facts and phenomena that actually occur using words and sentences or narrative. Based on the results of research conducted by researchers in the field, researchers can conclude that the marketing strategy used by SUA Snack to increase income is through promotions on social media, various discounts offered, attractive packaging, affordable prices and available in various flavors. As for the strengths, weaknesses, opportunities and threats that later emerged in SUA Snack in the marketing strategy carried out to increase income, the author carried out a SWOT analysis based on the results of interviews and observations in the field, namely Strengths such as good taste, affordable prices, friendly sellers and polite, attractive packaging, has many flavor variants, then Weaknesses: social media promotion is less than optimal, stock of goods is not large enough, and location is less strategic. Opportunities (Opportunities) in the culinary industry are popular with all groups, basreng and macaroni foods are currently viral, the taste is unique and addictive, can be enjoyed at any time and the last is Threat (Threat) such as the large number of food businesses appearing, high competitiveness, the perspective of some basreng people and Macaroni is neither healthy nor nutritious